(untitled) (The New Uzbekistan Journal of Medicine, 2025)
Fundamental scientific research is being actively conducted in the world today on the synthesis of polymer-metal complexes and the creation of promising drugs for different purposes. In this regard, it is an urgent task to obtain polymer-metal complexes with biological activity, to determine their physico-chemical properties and possible areas of their application. The purpose of the research: to obtain complexes of pectin with some metals and to study their physical and chemical properties.